(untitled) (R&E-SOURCE, 2025)
After completing primary school education, each of us is concerned with the question of what to do next, what direction to take, what job and related education to choose. Most often, these questions are addressed by adolescents before entering high school and university. Young generations are increasingly demanding in terms of the quality of education, employment, but above all the quality of their personal lives, and they much prefer their free time, where employment and financial resources are the means to fulfil this time and goals. Work (employment) is therefore not a priority for the youngest generations; rather, it is a means of self-realization. According to a Gallup poll in the US, 62% of adults of all ages would not choose the work they currently do if they could start over. (1997 NOICC/NCDA, Gallup Poll, USA). Choosing a profession is a crucial decision at the beginning of a professional career.